Masculinities, Gender Relations and Sport - Håkan Larsson (The Royal Danish Library, 2004)
Håkan Larsson anmelder "Masculinities, Gender Relations and Sport" af Jim McKay, Michael A. Messner og Don Sabo (eds.).